53 Korean Foods You Have to Try - Choi, Jia (Hollym, 2016)
Korean foods that are easy to make and rich in nutrition. The menus selected here are representations and characteristics of Korean cuisine. The recipes are healthy and simple to prepare. The cooking method is also quite simple and straightforward, so those attempting to make Korean food for the first time will not be met too many difficulties during cooking once the ingredients are ready. This book is divided into seven sections and each section is organized by the main ingredients. Moreover, any kind of chemical or artificial seasoning (e.g. MSG) is not included in the recipe. One can then enjoy the true, Korean flavor and original taste of the ingredients. Also, most of the ingredients that are introduced in this book are easily found in almost every grocery store. Moreover, one can adjust the level of spiciness and saltiness of the seasoning to one s taste. Introduction Ingredients \/ Korean\-Style Eating \/ Menu Planning for Korean Food \/ Choosing Dinnerware for Korean Food \/ What to Drink with Korean Food 1. The Basis of Hansik, Korean Food Myeolchi\-yuksu \/ Soegogi\-yuksu \/ Chaeso\-yuksu 2. Vegetable Dishes Rich in Dietary Fiber Ssam\-bap \/ Oi\-saengchae \/ Mu\-saengchae \/ Kong\-namul\-muchim \/ Dotori\-muk\-muchim \/ Beoseot\-bokkeum \/ Sigeumchi\-namul \/ Hobak\-namul \/ Japchae \/ Yeondubu \/ Dubu\-jorim \/ Nokdu\-bindae\-tteok \/ Bibim\-guksu \/ Kong\-guksu \/ Gamja\-sujebi \/ Sundubu\-jjigae 3. Seafood Dishes Packed with Iron and Mineral Godeungeo\-jorim \/ Ojingeo\-bokkeum \/ Myeolchi\-bokkeun \/ Kkotge\-tang \/ Miyeok\-guk \/ Haemul\-pajeon 4. Good Sources of Protein, Meat and Egg Dishes Bulgogi \/ Galbi\-gui \/ Galbi\-jjim \/ Dak\-galbi \/ Dak\-gangjeong \/ Jjim\-dak \/ Samgyetang \/ Bossam \/ Jaeyuk\-bokkem \/ Pyogobeoseot\-jeon \/Gyeran\-jjim \/ Yukgaejang 5. Gluten\-free, Rice and Rice Dishes Ssal\-bap \/ Chaeso\-gimbap \/ Bibimbap \/ Kimchi\-bokkeum\-bap \/ Hobak\-juk \/ Tteokguk \/ Tteok\-bokki 6. A Gold Mine of Vitamin, Kimchi and Fermented Foods Baechu\-kimchi \/ Oi\-sobagi \/ Kkakdugi \/ Geot\-jeori \/ Kimchi\-jeon \/ Dubu Kimchi \/ Kimchi\-jjigae \/ Doenjang\-jjigae 7. Nutritious Snacks and Desserts That Boost Your Happiness Sujeonggwa \/ Patbingsu \/ Hotteok \/ Yaksik Index